EDUKASI DAN PELATIHAN PRODUK WEBALUP DIABETES MELITUS PADA IBU-IBU LANSIA PKK MAWAR KUPANG PETE AMBARAWA KABUPATEN SEMARANG - I Kadek Bagiana; Yuvianti Dwi Franyoto; Mutmainah; Ika Puspitaningrum; Lia Kusmita (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2025)
Diabetes mellitus (DM) is a carbohydrate metabolism disorder characterized by high blood sugar levels (hyperglycemia). One alternative treatment to overcome diabetes is the use of herbal plants, one of which is moringa leaves (Moringa oleifera). Moringa leaves are rich in various nutrients, such as phytochemicals, carotene, flavonoid compounds, phenolic compounds, calcium, iron, protein, and vitamins. In addition, its antioxidant content plays a role in stabilizing free radicals, so it can function as a protector against diabetes mellitus. Based on its nutritional content, moringa leaves have many benefits. However, its use by elderly mothers in PKK Mawar Kupang Pete is still limited as a vegetable ingredient. This community service program focuses on socialization and training, both in theory and practice, in making Webalup (herbal tea) from moringa leaves into tea drink powder as an effort to increase endurance and reduce blood sugar levels. This activity was held on Saturday, September 7, 2024 in the RT hall with 30 PKK mothers as participants. The method used in this activity is Participatory Rural Appraisal (PRA), which actively involves the community in every stage of the activity. Based on the evaluation results, overall the participants were able to follow the training well, hold discussions with the community service team and were able to practice how to create a webalup.